2022
DOI: 10.1021/acs.jmedchem.1c01583
|View full text |Cite
|
Sign up to set email alerts
|

Elastase Inhibitor Cyclotheonellazole A: Total Synthesis and In Vivo Biological Evaluation for Acute Lung Injury

Abstract: Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is one of the most common complications in COVID-19. Elastase has been recognized as an important target to prevent ALI/ARDS in the patient of COVID-19. Cyclotheonellazole A (CTL-A) is a natural macrocyclic peptide reported to be a potent elastase inhibitor. Herein, we completed the first total synthesis of CTL-A in 24 linear steps. The key reactions include three-component MAC reactions and two late-stage oxidations. We also provided seven CTL-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…Moreover, they tested the synthesized Cyclotheonellazole A against human neutrophil elastase, showing an IC 50 value of 0.321 µM. Therefore, they proved that this compound is a more effective inhibitor against elastase than sivelestat (IC 50 = 0.704 µM), showing an inconsistent result compared with the previous study conducted by Issac et al; this is probably due to different experimental conditions, such as the source and concentration of the enzyme, the substrate and the time of incubation [ 45 , 46 ]. Elastase has recently been considered as a potential target for the prevention of ARDS in patients afflicted with SARS2-CoV-2 infection [ 14 ].…”
Section: Cyclic Peptides From Marine Spongesmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, they tested the synthesized Cyclotheonellazole A against human neutrophil elastase, showing an IC 50 value of 0.321 µM. Therefore, they proved that this compound is a more effective inhibitor against elastase than sivelestat (IC 50 = 0.704 µM), showing an inconsistent result compared with the previous study conducted by Issac et al; this is probably due to different experimental conditions, such as the source and concentration of the enzyme, the substrate and the time of incubation [ 45 , 46 ]. Elastase has recently been considered as a potential target for the prevention of ARDS in patients afflicted with SARS2-CoV-2 infection [ 14 ].…”
Section: Cyclic Peptides From Marine Spongesmentioning
confidence: 93%
“…Elastase has recently been considered as a potential target for the prevention of ARDS in patients afflicted with SARS2-CoV-2 infection [ 14 ]. The high elastase inhibitory activity of this compound could be particularly advantageous for patients with a D614G genotype infection [ 46 ].…”
Section: Cyclic Peptides From Marine Spongesmentioning
confidence: 99%
“…However, the overexpression of neutrophil elastase, which is a protease enzyme, is one of the main factors of lung consolidation and dysfunctional oxygenation in ARDS patients. Sivelestat, a neutrophil elastase inhibitor, reduces elastase activation and inhibits neutrophil aggregation by reducing the inflammatory response and the concentrations of IL-8 and tumor necrosis factor-α (TNF-α) (29)(30)(31). Numerous studies have concluded that sivelestat is therapeutically effective in treating ARDS, organ transplantation, tumors, and trauma (29,30,32).…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al describe the first total synthesis of cyclotheonellazole A, a natural macrocyclic peptide elastase inhibitor, in 24 linear steps. 19 Ashhurst et al show that the marine natural product, gallinamide A, and several synthetic analogues are potent inhibitors of cathepsin L, a key host cysteine protease important for viral entry. 20 Gallinamide A directly interacts with cathepsin L in cells and potently inhibits SARS-CoV-2 infection in the nanomolar range.…”
mentioning
confidence: 99%
“…Elastase is a serine protease that is mainly expressed on neutrophils and is an important cellular target to prevent acute lung injury/acute respiratory distress syndrome in COVID-19 patients. Cui et al describe the first total synthesis of cyclotheonellazole A, a natural macrocyclic peptide elastase inhibitor, in 24 linear steps . Ashhurst et al show that the marine natural product, gallinamide A, and several synthetic analogues are potent inhibitors of cathepsin L, a key host cysteine protease important for viral entry .…”
mentioning
confidence: 99%